Effect of exercise on the physiological norms of horses - Sandhya S (Department of Livestock Production Management, College of Veterinary and Animal Sciences, 1997)
In order to study the effect of exercise on the physiological norms of the horses, six horses belonging to the I (K) Mounted Squadron N.C.C. of Kerala Agricultural University were divided at random into groups of three animals. First was subjected to an exercise regime in the first month while the other remained as control. Groups were switched over every month. The parameters studied were body temperature, respiratory rate, heart beat, red blood cell count, packed cell volume, erythrocyte sedimentation rate, glucose and lactic acid, before exercise, after exercise and after one and half hours of rest. The results obtained are tabulated. ________________________________________________________ Parameters Before After After Exercise exercise rest Body temperature 37.72 + 0.064 39.06 + 0.027 38.08 + 0.116 (0C) Respiration rate 21.13 + 0.538 84.28 + 0.805 24.47 + 0.63 Per minute Heart beat per minute 36.19 + 0.083 66.57 + 1.32 41.63 + 1.53 RBO count per 7.29 + 0.049 8.03 + 0.039 7.44 + 0.0498 Million/cc PCV (%) 35.50 + 1.011 44.16 + 1.033 36.44 + 0.812 ESR mm/30 minutes 56.51 + 1.106 37.97 + 2.93 51.46 + 0.95 Glucose (mg%) 73.03 + 0.698 59.45 + 1.242 71.81 + 1.68 Lactic acid (mmol/L) 1.60 + 0.095 1.79 + 0.108 1.61 + 0.095 ________________________________________________________________